A Note on Separating Vectors for Operators on A HILBERT Space - Naoum, Adil; Al-Shimri, Zainab (Iraqi Journal of Science, 2025)
Let H and K be separable complex Hilbert spaces, and let B(H,K) be the space of bounded linear operators from H to K. If H=K we write B(H) for B(H,H).In this note we study separating vectors for separators on B(HK) that have representations of the form , where AB(H),BB(K) and CB(K,H).